The huntsman genus Decaphora Franganillo, 1931 (Araneae: Sparassidae: Sparianthinae) - Rheims, Cristina Anne; Alayón, Giraldo (Zootaxa, 2014)
The genus Decaphora Franganillo, 1931 is revised. Pseudosparianthis variabilis F.O. Pickard-Cambridge, 1900, Pseudosparianthis cubana Banks, 1909 and Thelcticopis pestai (Reimoser, 1939) are transferred to the genus; and P. cubana is considered a senior synonym of the type species, Decaphora trabiformis Franganillo, 1931. In addition, the female of T. pestai and the male of P. variabilis are described for the first time; and a new species, Decaphora kohunlich spec. nov., is described from Mexico and Guatemala.